Case Report: MDM4 Amplified in a Thymoma Patient With Autoimmune Enteropathy and Myocarditis - Du, Xin; Yu, Lei; Li, Fei; Yu, Zhen; Yang, Xing-guo; Jiang, Yu-xuan; Yu, Xin-tao (Frontiers in Endocrinology, 2021)
Introduction: Thymoma is a type of mediastinal malignant tumors which always associated with autoimmune diseases. Although surgery is the predominant treatment method for thymoma, the pathogenesis of thymoma and thymoma-associated autoimmune diseases is still unknow. However, the case study here provided a possible pathogenesis and treatment to cure the thymoma with autoimmune enteropathy and myocarditis. Case presentation: A thymoma case with autoimmune enteropathy and myocarditis undergoing surgery was reported. The symptoms and laboratory results of the patient had dramatically fluctuated after tumor resection and gradually alleviated. The whole exome sequencing found MDM4 amplified in tumor cells. Immunohistochemistry indicated that thymoma cells were positive for MDM4. The resul of drug sensitivity tests showed thymoma cells were highly sensitive to Nutlin-3a. Conclusion: MDM4 could play an important role in the pathogenesis of this thymoma case with autoimmune enteropathy and myocarditis. This discovery may provide a novel idea of pathogenesis and treatment for thymoma and autoimmune diseases.